Research on Gas Hydrate Plug Formation under Pipeline-Like Conditions - Florian Stephan Merkel; Carsten Schmuck; Heyko Jürgen Schultz; Timo Alexander Scholz; Sven Wolinski (International Journal of Chemical Engineering)
Hydrates of natural gases like methane have become subject of great interest over the last few decades, mainly because of their potential as energy resource. The exploitation of these natural gases from gas hydrates is seen as a promising mean to solve future energetic problems. Furthermore, gas hydrates play an important role in gas transportation and gas storage: in pipelines, particularly in tubes and valves, gas hydrates are formed and obstruct the gas flow. This phenomenon is called “plugging” and causes high operational expenditure as well as precarious safety conditions. In this work, research on the formation of gas hydrates under pipeline-like conditions, with the aim to predict induction times as a mean to evaluate the plugging potential, is described.